Extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE) among travellers to Africa: destination-specific data pooled from three European prospective studies - Tinja Lääveri; Jessica A. Vlot; Alje P. van Dam; Hanni K. Häkkinen; Gerard J. B. Sonder; Leo G. Visser; Anu Kantele (BMC Infectious Diseases, 2018)
Abstract Background One third of travellers to low- and middle-income regions of the tropics and subtropics become colonized by extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE). The risk varies by destination and, for each traveller, may be substantially further increased by travellers’ diarrhoea (TD) and antibiotic use. Despite the risk of TD in Africa, ESBL-PE acquisition rates in all studies are lower there than in Asia. Africa has become increasingly popular as a destination for international travellers, yet minimal data are available from the continent’s subregions and countries. Methods We analysed subregion- and country-specific data on carriage and risk factors for ESBL-PE colonization pooled from three prospective studies conducted between 2009 and 2013 among Finnish and Dutch travellers. The data were subjected to multivariable analysis of risk factors. In addition, we compared our data to two recent large investigations reporting data by subregion and country. Results Our joint analysis comprised data on 396 travellers. The ESBL-PE colonization rate was highest in Northern Africa, followed by Middle and Eastern Africa, and lowest in Southern and Western Africa. Of individual countries with more than 15 visitors, the highest rates were seen for Egypt (12/17; 70.6%), Ghana (6/23; 26.1%), and Tanzania (14/81; 17.3%); the rates among travellers to Egypt were comparable to those reported in South and Southeast Asia. In a pooled multivariable analysis, travel destination, age, overnight hospitalisation abroad, TD, and use of fluoroquinolones were independently associated with increased ESBL-PE colonization rates. Conlusions Even in areas with relatively low risk of colonization, antimicrobials clearly predispose to colonization with ESBL-PE. Travellers to Africa should be cautioned against unnecessary use of antibiotics.